2012
DOI: 10.1016/j.surfcoat.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of TiAlN/TiAlON/SiO2 absorber for solar selective applications

Abstract: Characterization of a TiAlN/TiAlON/SiO 2 tandem absorber is reported in this contribution. The first two layers were deposited by magnetron sputtering and the third layer was prepared by plasma enhanced chemical vapour deposition (PECVD). The optimization was performed by determining the optical constants of individual layers by first measuring spectral transmittance and reflectance of the individual layers. Subsequently the measuring spectra were fitted using the SCOUT software and dielectric function of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…2(a), TiAlN at low N 2 content shows metallic character and the optical constants were close to previous reports (Barshilia et al, 2006;Rebouta et al, 2012aRebouta et al, , 2012b. At lower N 2 content than 15%, the films are probably rich on metal elements and both the refractive index and the extinction coefficient are high.…”
Section: Optical Constants Of Individual Layerssupporting
confidence: 88%
See 1 more Smart Citation
“…2(a), TiAlN at low N 2 content shows metallic character and the optical constants were close to previous reports (Barshilia et al, 2006;Rebouta et al, 2012aRebouta et al, , 2012b. At lower N 2 content than 15%, the films are probably rich on metal elements and both the refractive index and the extinction coefficient are high.…”
Section: Optical Constants Of Individual Layerssupporting
confidence: 88%
“…solar absorbers due to their excellent chemical and mechanical stability, high oxidation resistance, and high degree of spectral selectivity (Xie and Hintzen, 2013). TiAlN/TiAlON/Si 3 N 4 ( Barshilia et al, 2006), TiAlN/AlON (Barshilia et al, 2008a), TiAlN/TiAlON/SiO 2 (Rebouta et al, 2012a), Ti 0.5 Al 0.5 N/Ti 0.25 Al 0.75 N/AlN (Du et al, 2011), TiAlON with TiC as buffer layer (Signore et al, 2011), and TiAlSiN/TiAlSiON/SiO 2 (Rebouta et al, 2012b) have been investigated as solar absorbers. The substrate used in these stack absorbers is generally copper because it preserves high thermal and electrical conductivity, and high infrared reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectra of the as-deposited coatings (a) and the tracks after tribological tests (b) are shown in Figure 8. The Raman spectrum of Ti-Al-N coatings is mainly determined by the vibrations of the heavy metal ions (typically 150-350 cm −1 ) and in the optic range by the vibrations of the lighter N ions (typically 550-650 cm −1 ) [40,41]. Two bands centered at ~225 and ~310 cm −1 corresponding to longitudinal and transversal acoustic (LA and TA) modes and one broad band at 560 cm -1 (LO and TO modes) are observed for the Ti-Al-N coating deposited at IAl = 70 A (Figure 8a).…”
Section: The Mechanical and Tribological Propertiesmentioning
confidence: 99%
“…Nyberg and Buhrman [50] reported a new physical property of coevaporated metal-dielectric films: the drastic increase in the surface roughness on Mo/Al 2 O 3 when the deposition temperature exceeds a certain minimum temperature. Rebouta et al [51] reported the characterization of TiAlN/TiAlON/SiO 2 tandem absorber; the first two layers were deposited by magnetron sputtering, and third layer was prepared by plasma-enhanced chemical vapor deposition (PECVD) and determined the optical constants of individual layers by first measuring spectral transmittance and reflectance of the individual layers. Du et al [52] designed a new solar selective coating, Ti 0.5 Al 0.5 N and Ti 0.25 Al 0.75 N coatings were chosen as absorber layers, and AlN coating was chosen as anti-reflecting layer and calculated the absorptance 0.945 and low emittance 0.04 (82°C) of the solar selective coating.…”
Section: Solar Spectral Selective Mechanismsmentioning
confidence: 99%